Relevance Of Justice Value In Legal Protection Of Debtor In The Political Law Of Bankruptcy - Budisidhabhiprodjo Budisidhabhiprodjo (Jurnal Akta, 2020)
In its development the business world requires the provision of capital loan services. However, the development of the need for capital in the business world is not balanced with protection for debtors. The existence of Articles 55 and 56 of Act Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, the position of debtor protection in the bankruptcy undertaken by a separatist creditor against the creditor becomes weak, this is due to the absence of legal remedies that can be done by the dbitur when bankruptcy has been declared effective against him. Therefore the issues that will be discussed in this journal are the legal protection system for debtors in bankruptcy politics, weaknesses in the legal protection system for debtors in bankruptcy political politics, and issues related to finding solutions through reforming the legal protection system for debtors in bankruptcy politics.The purpose of this research is to analyze the legal protection system for debtors in bankruptcy law politics; to analyze the weaknesses of the legal protection system for debtors in bankruptcy law politics; to find a solution through reforming the legal protection system for debtors in bankruptcy law politics.The research method  used in this paper is a normative juridical approach. As for the research that has been done, it can be concluded that the existence of Article 55 and Article 56 of Act Number 37 of 2004 concerning Bankruptcy and Delaying Obligations of Debt Payment has resulted in injustice to debtors in the implementation of bankruptcy against debtors committed by creditors; So it is necessary to reform the implementation of debtor protection in the implementation of bankruptcy to debtors by the creditor by implementing a system of debtor protection in the implementation of bankruptcy to debtors based on Pancasila. Keywords: Debtor; Justice Value; Legal Protection; Legal Politics; Bankruptcy.